PENANAMAN NILAI KARAKTER DALAM PEMBELAJARAN ANAK SD MELALUI CERITA RAKYAT SARIDIN - Sari, Syibilla Oktavia Malaka; Ulhaq, Jessica Dhiya'; Eka Putri, Hasna Dyah; Fatmasari, Diah; Rohmah, Nihayatur; Kanzunnudin, Mohammad (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The process of learning character education for elementary school children is an important thing in the world of education. Instilling character values ​​is not only in the family environment, but anywhere, for example at school. Children will know the character values ​​obtained through the learning process at school. This research was conducted with the aim of teaching character values ​​to elementary school students through the folklore "Saridin". The folk tale "Saridin" comes from Pati Regency, Kayen Village. This research was conducted with the aim of teaching character values to elementary school students. The method taught in this study is a qualitative method, using observation, interviews, as data collection techniques. The results of the research show that Saridin’s story contains several character values, including the values of divinity, nationalism, independence, and mutual cooperation. Implementation of the values of Saridin’s story in basic education can help students develop positive character and skills, and have positive impact on students’ daily lives. Keywords: character value, folklore, Saridin